Tris (2-chloroethyl) phosphate (TCEP) induces obesity and hepatic steatosis via FXR-mediated lipid accumulation in mice: Long-term exposure as a potential risk for metabolic diseases. (25th August 2022) - Yang, Daqian; Wei, Xiangjuan; Zhang, Ziyi; Chen, Xi; Zhu, Ruijiao; Oh, Yuri; Gu, Ning
Abstract: Tris (2-chloroethyl) phosphate (TCEP) is the most commonly detective organophosphate flame retardant in surroundings. TCEP is also evidenced as endocrine disrupting chemicals and has potential adverse effects on metabolic diseases. In this study, we hypothesized that metabolic diseases are adverse outcomes of TCEP exposure. Adult ICR mice was daily treated with TCEP (20 mg/kg and 60 mg/kg, higher than expected level in people) by gavage administration for 9 weeks. The results demonstrate that TCEP promoted body weight gain, hypertriglyceridemia, and hepatic steatosis, consistent with upregulation of hepatic lipogenesis-related gene expression. Moreover, TCEP altered the levels of several hepatic metabolites, especially bile acids and downregulated bile acid synthesis pathways. Intriguingly, we found a marked downregulation of the bile acid nuclear reporter, FXR, in TCEP-exposed livers. Mechanistically, TCEP directly interacted with FXR at Lys335 and Lys336. Further studies in this work elucidate the mechanisms of long-term TCEP exposure on hepatic steatosis and obesity in mice via FXR-mediated lipid accumulation. Our results provide insight into the possibility of intermediate TCEP exposure in causing metabolic diseases. Graphical abstract: Image 1 Highlights: TCEP induces obesity, hyperlipidemia, liver injury and hepatic steatosis. TCEP disturbs bile acid homeostasis, resulting in hepatic FXR inactivation. FXR inhibition promotes hepatic steatosis via lipogenesis and lipid oxidation. FXR activator CDCA reverses TCEP-induced obesity, hyperlipidemia, and hepatic steatosis. Abstract : Impact statement: This study demonstrates that exposure to TCEP is relevant to rising risks of metabolic diseases, including obesity, hyperlipemia and hepatic steatosis, via altering the balance of bile acids and inhibiting its receptor FXR.